"Emberpiac" a Moszkva téren - Sik, Endre (Szociológiai Szemle, 2024)
In Hungary part of the „classical” odd jobs (labour for a few hours or days) is distributed in the so-called „slave markets”. In 1997 and in 1998 approximately in every fifth Hungarian village, or town there was such a market, which is somewhat higher than the value calculated in 1995 (18%).The characteristics of the Moszkva Square slave market are the following on the basis of anthropological observation:- the Square „opens” at 5 a.m., the largest number of job-seekers are present at about a7 a.m., and by about noon the Square practically stops functioning as a slave market.- spring and summer are the busiest periods of the slave market,- the employers are characteristically the building entrepreneurs of the nearby elite residential .areas,- the work to be performed is usually the simplest unskilled labour,- the majority of job-seekers are Hungarians from abroad, males, many of them are homeless and poor,- wages are low and hardly grow.The technique of research was non-participant observation. The occasions of observation (84) were distributed between April 1995 and March 1996, so that they may be representative of the day, season and period of the day of observation. An observation lasted for two hours. In the initial and final phases of observation (taking up maximum five to ten days) the number of job-seekers present in Moszkva Square and the conditions of observation (weather, presence of police) had to be recorded. During the time in between (more than one and a half hours) the observer had two further tasks:- 20-20 job-seekers had to be chosen randomly and their observable characteristics recorded,- as many transactions as possible had to be recorded (offer, bargain, agreement, characteristics of the participants of transaction).According to our observations only about 300 job-seekers turn up on an average market day (between 5 a.m. and 12 o’clock) at the slave market of Moszkva Square, and there are not many more successful transactions than 10-20 a day. It means that the function of the Moszkva Square slave market is the „production” of cheap unskilled labour for the building industry of Budapest.